Establishing the influence of grinding modes on different thicknesses of furniture panels - Petryshak, I.V.; Gayda, S.V.; Humeniuk, Zh.Ya. (Forestry, Forest, Paper and Woodworking Industry, 2023)
Literary sources on the influence of different thicknesses of furniture blanks on the stability of the grinding tool were analyzed. The relevance of processes of grinding wooden surfaces is considered. Problems of different thicknesses of furniture panels are described. The main problems of wear resistance of grinding tools are considered. A methodology for studying the effect of different thicknesses of furniture blanks on the stability of the grinding tool during the processing of furniture boards made of beech wood and pine wood has been developed. Regression dependences were obtained that describe the state of the thickness of furniture species made of beech and pine depending on the speed of cutting with an abrasive and the pressure of the sandpaper. It was established that the clamping force of the grinding wheel affects more than the cutting speed, and the minus sign in the second factor (clamping force) shows a decrease in the accuracy of the furniture board. It was found that with an increase in the abrasive cutting speed of the glued surface of the furniture panel made of beech wood, the thickness variation of the panel construction increases by 320-622%, and for the glued surface of the furniture panel made of wood, the thickness variation of the panel construction increases by 55-80%. It was established that with an increase in the force of clamping the workpiece to the glued surface of the furniture board made of beech wood, the specific productivity of the sandpaper increases by 48.82-62.63%, and with a decrease in the size of the grains of the abrasive tool, the specific productivity of the sandpaper decreases by 39.27-90.74% . It was determined that with an increase in the clamping force of the workpiece to the glued surface of the furniture board made of pine wood, the specific productivity of the sandpaper increases by 42.90-53.64%, and with a decrease in the grain size of the abrasive tool, the specific productivity of the sandpaper decreases by 79.37-120.94%. Ways to increase the stability of the grinding tool during the processing of furniture panels of various designs are proposed.